2006
DOI: 10.1175/waf981.1
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Statistical Downscaling for Rainfall Forecasting over Southeastern Brazil

Abstract: In this work linear and nonlinear downscaling are developed to establish empirical relationships between the synoptic-scale circulation and observed rainfall over southeastern Brazil. The methodology uses outputs from the regional Eta Model; prognostic equations for local forecasting were developed using an artificial neural network (ANN) and multiple linear regression (MLR). The final objective is the application of such prognostic equations to Eta Model output to generate rainfall forecasts. In the first exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…The critical role of high-resolution gridded rainfall data sets for hydrological simulations has led to the development of several rainfall disaggregation algorithms (e.g., Brussolo et al, 2008;Ferraris et al, 2003;Fowler et al, 2007;Frei et al, 2006;Maraun et al, 2010;Ning et al, 2011;Park, 2013;Rahman et al, 2009;Ramírez et al, 2006;Tao and Barros, 2010). The main assumption for some recently developed downscaling methods for satellite-based products is the relationship between spatial variability of rainfall and environmental factors such as topography and land surface conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of high-resolution gridded rainfall data sets for hydrological simulations has led to the development of several rainfall disaggregation algorithms (e.g., Brussolo et al, 2008;Ferraris et al, 2003;Fowler et al, 2007;Frei et al, 2006;Maraun et al, 2010;Ning et al, 2011;Park, 2013;Rahman et al, 2009;Ramírez et al, 2006;Tao and Barros, 2010). The main assumption for some recently developed downscaling methods for satellite-based products is the relationship between spatial variability of rainfall and environmental factors such as topography and land surface conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One can see that in both downscaling methods used the highest correlations occur in winter in all regions under study, indicating that the models are better able to represent the variability of precipitation during this season. Ramírez et al (2006) performed statistical downscaling for the precipitation forecast for the southeast of Brazil, using ANNs and MLR with the ETA model. The results suggested that the precipitation forecasts using ANNs performed better in winter than in summer, since the synoptic forcing is more pronounced and the deep convective activity is less common.…”
Section: Validation Of the Mlr By Pcsmentioning
confidence: 99%
“…Dynamic techniques focus on numerical models with more detailed resolution, while statistical (or empirical) techniques use transfer functions between scales. Currently, numerical weather prediction (NWP) models can forecast various meteorological variables with acceptable accuracy (Ramírez et al, 2006). Specifically, rainfall is of great interest, both for its climatic and meteorological relevance and for its direct effect on agricultural output, hydropower generation, and other important economic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it performed slightly better for simulating monthly total precipitation with correlation coefficient of 0.65. Later, Ramirez and Ferreira, (2006) have compared the ANN and MLR approaches to downscale rainfall in Eta region of Brazil. They concluded that ANN has tendency to forecast moderate and high rainfall with greater accuracy during the austral summer and was superior to multiple linear regression (MLR).…”
Section: Introductionmentioning
confidence: 99%